Prácticas de enseñanza de iniciación a la lecto- escritura en primer año de educación general básica en una unidad educativa religiosa - Córdova Cevallos, Lorena Elizabeth (2016)
This case study yielded information on teaching practices initiation to literacy in First Year of General Basic Education in a religious educational unit, with children aged 5 to 6 years. This research will observe the performance of teachers inside and outside the classroom, interaction with students and management planning in the area of reading and writing, because the interrelationships and actions that occur in that area have been modified and adapting to the context allowing interest to conduct an investigation. To perform this qualitative research method was used with the support of an observation sheet as a tool, a semi-structured interview and a field journal. This research includes the following aspects: presentation and description of the problem, objectives, theoretical foundation where they develop more broadly investigated the two issues are: Practices of Teaching and Literacy; finally the results obtained during the investigation through conclusions are analyzed.